Quantification of Leptospira interrogans Survival in Soil and Water Microcosms - Casanovas-Massana, Arnau; Pedra, Gabriel Ghizzi; Wunder, Elsio A.; Diggle, Peter J.; Begon, Mike; Ko, Albert I. (Applied and environmental microbiology, 2018)
Leptospira interrogans is the etiological agent of leptospirosis, a globally distributed zoonotic disease. Human infection usually occurs through skin exposure with water and soil contaminated with the urine of chronically infected animals. In this study, we aimed to quantitatively characterize the survival of Leptospira interrogans serovar Copenhageni in environmental matrices. We constructed laboratory microcosms to simulate natural conditions and determined the persistence of DNA markers in soil, mud, spring water and sewage using a quantitative PCR (qPCR) and a propidium monoazide (PMA)-qPCR assay. We found that L. interrogans does not survive at high concentrations in the tested matrices. No net growth was detected in any of the experimental conditions and in all cases the concentration of the DNA markers targeted decreased from the beginning of the experiment following an exponential decay with a decreasing decay rate over time. After 12 and 21 days of incubation the spiked concentration of 10 6 L. interrogans cells/ml or g decreased to approximately 100 cells/ml or g in soil and spring water microcosms, respectively. Furthermore, culturable L. interrogans persisted at concentrations under the limit of detection by PMA-qPCR or qPCR for at least 16 days in soil and 28 days in spring water. Altogether, our findings suggest that the environment is not a multiplication reservoir but a temporary carrier of L. interrogans Copenhageni, although the observed prolonged persistence at low concentrations may still enable the transmission of the disease. IMPORTANCE Leptospirosis is a zoonotic disease caused by spirochetes of the genus Leptospira that primarily affects impoverished populations worldwide. Although leptospirosis is transmitted by contact with water and soil, little is known about the ability of the pathogen to survive in the environment. In this study, we quantitatively characterized the survival of L. interrogans in environmental microcosms and found that although it cannot multiply in water, soil or sewage, it survives for extended time periods (days to weeks depending on the matrix). The survival parameters obtained here may help to better understand the distribution of pathogenic Leptospira in the environment and improve the predictions of human infection risks in areas where such infections are endemic.